New method of measuring µ-focus spots of X-ray tubes; Journal of Physics: Conference Series; Vol. 881 : Innovations in Non-Destructive Testing (SibTest 2017) - Gnedin M.; Usachev E.; Valikov V.; Gheveler V.; Stein A. M. Aleksandr Mikhailovich (2017, 2017)
Title screen